Adherence to Mediterranean Diet and Ocular Dryness Severity in Sjögren’s Syndrome: A Cross-Sectional Study - Celine Chaaya; Elie Raad; Francesca Kahale; Elias Chelala; Nelly Ziade; Georges Maalouly (Medical Sciences, 2025)
Background: Sjögren’s syndrome (SS) is a multifaceted clinical condition characterized by various features, including ocular dryness (OD), which plays a substantial role in shaping the clinical presentation of the disease and has detrimental effects on quality of life. Recent research has acknowledged the advantages of the Mediterranean diet (MD) for its positive impact on various autoimmune diseases. This study aims to investigate the correlation between the severity of ocular symptoms in individuals with SS and adherence to the MD. Methods: This was a cross-sectional observational study of previously diagnosed SS patients recruited from the histopathological and immunological archives of a university hospital. The data were collected through a telephone questionnaire, including demographic and disease data, the Ocular Surface Disease Index (OSDI) score to evaluate the OD severity, and the Mediterranean Diet Adherence Screener (MEDAS) score to determine adherence to the MD. The primary outcome of the study, the correlation between OSDI and MEDAS scores, was evaluated using Spearman’s correlation coefficient. Results: The study included 114 patients, with a mean age of 51 (±13.4) years and a female proportion of 86%. OD was documented in 80.7% of the patients. The median OSDI and MEDAS scores were 23 (IQR 10–40) and 8 (IQR 5–11), respectively. A strong negative correlation was observed between the MEDAS and the OSDI scores (ρ = −0.73, p < 0.01). Additionally, there was a significant negative relationship between the richness of diet in fatty acids and the OSDI score (ρ = −0.67, p < 0.01). Conclusions: The study results suggest an association between lower OD severity in patients with SS and adherence to the MD, particularly the components related to polyunsaturated fatty acids consumption. This approach may serve as a complementary strategy with multiple health benefits, alongside conventional treatment options.